The Effect of Sharia Supervisiory Board Size and the Health Ratio of Bank Sharia to Profitability - Prisylia Putri; Iwan Fakhruddin; Suryo Budi Santos; Nur Isna Inayati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study to analyze the effect of the SSB size and financial performance on profitability as measured using Return On Assets (ROA) in Islamic public banking in Indonesia for the 2017-2021 period and prove the hypothesis. Quantitative descriptive research method using secondary data obtained from the official financial reports of each Islamic Commercial Bank. Purposive Sampling was used in this study, so that the number of samples was 11 Islamic Commercial Banks. The statistical test results show that the DPS, CAR, NPF and BOPO variables each have a negative effect on ROA. While the FDR variable has no effect on ROA.